2012
DOI: 10.4018/jitr.2012070101
|View full text |Cite
|
Sign up to set email alerts
|

Success Factors for ICT Shared Services in the Higher Education Sector

Abstract: Shared services is a prominent organizational arrangement for organizations, in particular for support functions. The success (or failure) of shared services is a critical concern as the move to shared services can entail large scale investment and involve fundamental organizational change. The Higher Education (HE) sector is particularly well poised to benefit from shared services as there is a need to improve organizational performance and strong potential from sharing. Through a multiple case study of share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…This is consistent with the literature (Aksin and Mansini, 2008; El Sawy et al. , 2010; Miskon et al. , 2012) in which STAN is identified as a core element.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with the literature (Aksin and Mansini, 2008; El Sawy et al. , 2010; Miskon et al. , 2012) in which STAN is identified as a core element.…”
Section: Discussionsupporting
confidence: 93%
“…Third, addressing STAN, it can be noticed that this condition is present in three out of seven solutions while once as a core condition (see Table 4). This is consistent with the IMDS 122,4 literature (Aksin and Mansini, 2008;El Sawy et al, 2010;Miskon et al, 2012) in which STAN is identified as a core element. Interestingly, when the size of firms was included in the analysis (see Table 6), the presence of this condition appeared only once.…”
Section: Theoretical Implicationssupporting
confidence: 91%
See 1 more Smart Citation
“…The findings of the context definition phase and exploratory phase formed a firm basis in the multiple and exploratory phase created a strong foundation in the stage of various case studies intended to tackle this study's main objectives. Miskon, Bandara and Fielt (2017) conducted a case study of shared services in the exploration of Malaysian Higher Education sector. The research performed an empirical exploration of five main categories: economic, technical, process improvement, strategic and organizational advantages, and political advantages.…”
Section: Information Communication Technology Shared Service and Financial Performancementioning
confidence: 99%
“…Government of Malaysia through Ministry of Higher Education (MOHE) has initiated the shared services implementation within Higher Education (HE) sector. A recent study has identified ten success factors in HE sector as discussed below by [27]:…”
Section: Malaysiamentioning
confidence: 99%